Phenytoin-Folate Interactions: How Far is Safe Folate Supplementation in Phenytoin Treated Epileptic Patients? - Abhishek Singh Nayyar, B. Nataraju, G. T. Subhas (Journal of Applied Pharmaceutical Science)
Chronic administration of phenytoin has been associated to have a number of adverse effects. Falling serum folate levels is one such most often reported adverse drug sequelae of long term phenytoin usage. Folates administered at pharmacological doses, on the other hand, have been blamed for a decrease in the serum concentration of phenytoin, severe enough to precipitate seizures. This review substantiated with references from various studies focuses on the folic acid-phenytoin interaction and discusses the feasibility of using folate supplements to avoid such inadvertent drug sequelae in epileptic patients kept on chronic treatment with phenytoin.
Keywords: Phenytoin, anti-convulsant, folate metabolism, seizures.